SISTEM AGROFORESTRI DATARAN TINGGI DAN DATARAN RENDAH KABUPATEN MINAHASA SELATAN PROVINSI SULAWESI UTARA - Suli, Andreas A.T.; Husain, Jailani; Walangitan, Hengki D. (EUGENIA, 2018)
ABSTRACTÂ South Minahasa Regency have a topography that varied from lowland to highland. Until now there has been no research on differences in the performance of agroforestry systems of lowland and highland agroecological zones. The purposes of this study were to analyze the diversity of plant species and to estimate the biomass amount of agroforestry systems at lowland and highland agroecological zones. The research was carried out from October to December 2017 at two different agroecological zones, namely; the highland (Mokobang Village) and the lowland (Blongko Village). The results showed that there were 21 plant species at lowland having 4 plant species in average, while 30 plant species were found in the highland with 6 plant species in average. The biomass of 0.25 to 13.11 Mg ha-1 with an average of 3.47 Mg ha-1 was found at lowland, whereas the highland contained 0.34 to 98.65 Mg ha-1 with an average of 27.40 Mg ha-1 biomass. It is concluded that in South Minahasa Regency the highland agroforestry system had more plant species and had more carbon sequestration than that of lowland.Keywords : agroforestry, highland zone, lowland zone